Digital Banking Adoption among Households in Nepal: An Empirical Analysis (Patan Pragya, 2024)
This study analyzes the determinants of Digital Banking Adoption in Nepal, focusing on households in the Patan area of Lalitpur. Utilizing the Technology Acceptance Model (TAM), the research investigates the roles of perceived risk, performance expectancy, belief, and social influence in shaping user behavior. Data were collected through structured questionnaires from 355 respondents and analyzed using descriptive and inferential statistics, including correlation and regression analysis. The findings highlight that belief is the most significant predictor of Digital Banking Adoption, emphasizing the critical role of trust in fostering user confidence. Performance expectancy also plays a vital role, demonstrating that efficiency and functionality significantly influence adoption decisions. Social influence, particularly in Nepal’s collectivist culture, further enhances adoption through peer and familial recommendations. Perceived risk, while a lesser factor, underscores the importance of addressing security concerns to encourage broader adoption. The study provides invaluable insights for financial institutions and policymakers to improve digital banking services, enhance user trust, and leverage community dynamics to drive digital financial inclusion. The findings contribute to the broader discourse on the intersection of technology adoption and financial inclusion in developing economies like Nepal.